Effective treatment for malignant mediastinal teratoma. - Parker, D (1983)
Primary malignant mediastinal teratoma is a rare tumour previously regarded as inevitably fatal. In a series of eight male patients with a mean age of 24 years five remain alive and well. All patients showed raised serum concentrations of human chorionic gonadotrophin or alpha fetoprotein. The patients were treated with intermittent combination chemotherapy that included cisplatin. Six patients responded to chemotherapy with a fall in human chorionic gonadotrophin or alpha fetoprotein to near normal levels and they then had radical excision of the remaining tumour. Living malignant tumour was found in four of the specimens and these patients received postoperative chemotherapy. One patient died after eight months and the remaining five patients are alive and well 13-136 months after the start of treatment. The two patients who did not undergo surgery died at one month and 15 months. Intermittent combination chemotherapy and carefully timed radical excision of these tumours would appear to have produced better results than have been reported in other series.